Developing a Shariah-compliant model of dental and maxillofacial surgery care: a tertiary hospital experience - Chi Adam, Khairul Bariah; Harun, Nor Adilah; Hassan, Haszelini; Subramaniam, Pram Kumar; Ismail, Izzati Nabilah; Mustafa, Naziyah Shaban (Faculty of Medicine, UKM, 2025)
Introduction: A Shariah-compliant hospital embodies Islamic ethics in healthcare, aiming to provide treatment grounded in dignity, compassion, and holistic well-being. The Dental & Maxillofacial Surgery (DMFS) Unit at Sultan Ahmad Shah Medical Centre @IIUM (SASMEC@ IIUM) integrates the tawhidic paradigm and Islamisation of knowledge, framing clinical practice, ethics, and community service within Qur’anic and Prophetic principles. This presentation outlines the development of the DMS Unit, focusing on its Shariah-compliant framework, integration of tawhidic values in patient care and education, community outreach, and technological innovation. Methods: The establishment of the DMS Unit was implemented in two phases. Phase 1 focused on internal development-building a multidisciplinary team comprising oral and maxillofacial surgeons, pediatric dentists, special needs, restorative, and prosthodontic specialists. Services progressed from outpatient care to major surgeries, guided by Shariah principles such as halalcertified materials, gender chaperoning, and aurah protection. Continuous training included both clinical sub-specialisation and fiqh-based healthcare education to embed Islamic jurisprudence into daily practice. Phase 2 emphasised collaboration and outreach through partnerships with Oncology, ENT, Plastic Surgery, and community initiatives like Smile-A Tonne and Pacific Partnership. Outreach combined oral health promotion with spiritual and da‘wah elements, while technological innovation introduced virtual surgical planning, 3D printing, and navigation-assisted surgery within an ethically grounded tawhidic framework. Results: The unit expanded its clinical scope, enhanced interdisciplinary collaboration, and strengthened community engagement while maintaining Shariah compliance. Digital innovations improved precision, efficiency, and cost-effectiveness, reinforcing the tawhidic approach as a model for Islamisation in healthcare. Conclusion: The DMS Unit at SASMEC@IIUM exemplifies how a Shariah-compliant, tawhidic approach in dental and maxillofacial care can harmonise faith, ethics, and technology-embodying Ihsan, the Qur’anic principle of excellence in service.